Aerodynamic pressures around high-speed trains: the transition from unconfined to enclosed spaces. (November 2013) - Gilbert, Timothy; Baker, Christopher; Quinn, Andrew
The theory and practice of train-induced aerodynamic pressure loads on surfaces near to the tracks is compromised by an incomplete understanding of trains operating in short tunnels, partially enclosed spaces, and next to simple structures such as vertical walls. Unique pressure-loading patterns occur in each case. This work has been carried out to obtain a fundamental understanding of how these loading patterns transition from one to the other as the infrastructure becomes more confined. It also considers the impact of the results on two separate European codes of practice applying to tunnels and other structures. A parametric moving-model study was undertaken, transitioning from the open air to single and double vertical walls, partially enclosed spaces, short single-track tunnels and a longer tunnel. The train model was based on a German ICE2, and was fired at 32 m/s past the structures. Multiple surface pressure tappings and in-flow probes were used, providing the opportunity to assess the three-dimensional nature of the pressure and velocity fields. The experiments successfully mapped the transition between the three loading patterns and isolated the geometric changes. Further loading patterns were discovered relating to the length of the train, the length of the tunnel and the distance from the tunnel entrance. The three-dimensional nature of the pressure was related to the length of the tunnel and the distance from the tunnel entrance. Issues surrounding the lack of provision in codes of practice for short tunnels were discussed.